1977
DOI: 10.1016/s0022-5347(17)58277-4
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Lymphoma of the Testis: A Clinicopathologic Study of 37 Cases

Abstract: The clinicopathologic findings in 37 cases of malignant lymphoma with primary clinical manifestation in the testis were analyzed. Of these cases 34 were classified as histiocytic lymphoma and 3 as lymphocytic lymphoma. Patients usually presented with a painless small testicular mass of short duration. The peak incidence occurred in the fifth through eighth decades. Metachronous testicular involvement was noted in 35 per cent of the cases and simultaneous bilateral involvement in 3 per cent. In 25 per cent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(37 citation statements)
references
References 10 publications
1
35
0
1
Order By: Relevance
“…TNHL has a predilection for spreading to non-contiguous extranodal sites, especially the central nervous system (CNS). [1][2][3][4][5][6] The majority of reported TNHL cases present diffuse histology, and usually B-cell type. 1,3,4,[7][8][9] As it is a rare tumor, and population-based studies are few, its treatment is controversial, especially regarding its early stage.…”
Section: Introductionmentioning
confidence: 99%
“…TNHL has a predilection for spreading to non-contiguous extranodal sites, especially the central nervous system (CNS). [1][2][3][4][5][6] The majority of reported TNHL cases present diffuse histology, and usually B-cell type. 1,3,4,[7][8][9] As it is a rare tumor, and population-based studies are few, its treatment is controversial, especially regarding its early stage.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported the incidence of bilateral involvement of about 10-40%. [1][2][3][4][5][6][7]12,15 …”
Section: Affected Age Group and Bilateralitymentioning
confidence: 99%
“…1,4,6,9 TNHL has a predilection for dissemination to non-contiguous extranodal sites such as the CNS, Waldeyer's ring, skin and lungs. 1,4,10,12 Martenson et al reported a 10% incidence of CNS involvement in the initial failure and 20% in subsequent relapses.…”
Section: Etiological Factors and Dissemination Patternsmentioning
confidence: 99%
See 2 more Smart Citations